Effect of Five Polymorphisms on Percentage of Oleic Acid in Beef and Investigation of Linkage Disequilibrium to Confirm the Locations of Quantitative Trait Loci on BTA19 in Japanese Black Cattle - Fuki Kawaguchi; Fuka Kakiuchi; Kenji Oyama; Hideyuki Mannen; Shinji Sasazaki (Life, 2021)
Five polymorphisms associated with the percentage of oleic acid (C18:1) in beef fat were previously reported on bovine chromosome 19 in different Japanese Black cattle populations. This study aimed to verify the effects of these five polymorphisms on C18:1 using the same Japanese Black cattle population and conduct linkage disequilibrium (LD) analysis in order to determine the locations of the quantitative trait loci (QTLs). We genotyped the five polymorphisms (SREBP1 c.1065 + 83 (84bp indel), STARD3 c.1187 C > T, GH c.379 C > G, FASN g.841 G > C, and FASN g.16024 A > G) in two populations, which were bred in Hyogo and Gifu Prefectures, Japan (n = 441 and 443, respectively) in order to analyze their effects on C18:1 using analysis of variance (ANOVA). In the Hyogo population, SREBP1 c.1065 + 83 and STARD3 c.1187 C > T were significantly associated with C18:1 (p < 0.001). Meanwhile, FASN g.841 G > C, FASN g.16024 A > G, and GH c.379 C > G were significantly associated with C18:1 (p < 0.01) in the Gifu population. LD analysis was subsequently conducted to detect the range of the QTLs, which ranged from 32.2 to 46.4 Mbp and from 47.8 to 52.1 Mbp in the Hyogo and Gifu populations, respectively. In conclusion, this study confirmed the existence of QTLs on BTA19 and divided the candidate region for each QTL based on LD coefficients. These results could contribute to efficient searches for responsible genes and polymorphisms for fatty acid composition.